Serological and cellular response to mRNA-SARS-CoV2 vaccine in patients with hematological lymphoid malignancies: Results of the study “Cervax” - Mohamed, Sara; Lucchini, Elisa; Sirianni, Francesca; Porrazzo, Marika; Ballotta, Laura; Ballerini, Mario; De Sabbata, Giovanni Maria; De Bellis, Eleonora; Cappuccio, Ilaria; Granzotto, Marilena; Toffoletto, Barbara; Fortunati, Ilaria; et al. (Frontiers in Oncology, 2023)
messenger RNA (mRNA)-Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) vaccines such as BNT162b2 became available in late 2020, but hematological malignancy patients (HM pts) were not evaluated in initial registration trials. We hereby report the results of a prospective, unicentric, observational study Response to COVID-19 Vaccination in hEmatological malignancies (CERVAX) developed to assess the postvaccine serological and T-cell-mediated response in a cohort of SARS-CoV2-negative HM pts vaccinated with BNT162b2. Patients with lymphomas [non-Hodgkin lymphoma (NHL) and Hodgkin lymphoma (HL)], chronic lymphocytic leukemia (CLL), and multiple myeloma (MM); off-therapy for at least 3 months; in a watch-and-wait program; or in treatment with ibrutinib, venetoclax, and lenalidomide were included. Different time points were considered to assess the serological response to the vaccine: before the second dose (T1), at 3–6–12 months after the first dose (T2–3–4, respectively). Since March 2021, 39 pts have been enrolled: 15 (38%) NHL, 12 (31%) CLL, and 12 (31%) MM. There were 13 of the 39 pts (33%) seroconverted at T1; an increase of the serological response was registered after the second dose (T2) (22/39 pts, 56%) and maintained after 6 months (22/39 pts, 56%) and 12 months (24/39 pts, 61%) from the first dose (T3–T4, respectively). Non-serological responders at T4 were 7/39 (18%): 0/15 NHL, 1/12 MM (8%), and 6/12 CLL (50%). All of them were on therapy (one lenalidomide, three ibrutinib, and three venetoclax). SARS-CoV2-reactive T-cell analysis (interferon gamma release assays) was available since June 2022 and was evaluated at 12 months (T4) from the first dose of vaccine in 31/39 pts (79%). T-cell-mediated-responders were 17/31 (55%): most of them were NHL and MM (47%, 41% and 12% for NHL, MM, and CLL, respectively). Both serological and T-cell non-responders were represented by pts on active therapy (venetoclax/ibrutinib). During the period of observation, eight (20.5%) pts developed mild SARS-CoV2 infection; no coronavirus disease 19 (COVID-19)-related deaths or hospitalizations were registered. In conclusion, in our cohort of lymphoproliferative pts receiving BNT162b2, CLL diagnosis and venetoclax/ibrutinib seem to be related with a lower humoral or T-mediated response. Nevertheless, the efficacy of mRNA vaccine in HM pts and the importance to continue the vaccine program even in non-responders after the first dose are supported in our study by demonstrating that a humoral and T-cell-mediated seroconversion should be observed even in the subsets of heavily immunocompromised pts.